2001
DOI: 10.3168/jds.s0022-0302(01)74518-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solar Radiation and Feeding Time on Behavior, Immune Response and Production of Lactating Ewes Under High Ambient Temperature

Abstract: A 6-wk trial was performed with 40 late-lactation Comisana ewes, which were either exposed to or protected from solar radiation and fed either in the morning (EXPM, PROM) or afternoon (EXPA, PROA) during summer in a Mediterranean climate. Behavioral traits of ewes were recorded once per week from 0800 to 2000 h. Rectal temperature (RT) and respiration rate (RR) were measured twice weekly at 1430 h. The phytohemagglutinin (PHA) skin test was performed to induce nonspecific delayed-type hypersensitivity at d 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(108 citation statements)
references
References 20 publications
3
102
1
2
Order By: Relevance
“…As mentioned by Daviau et al (2008), the shorter RCT was associated with a decrease in P content and also of casein. It was found out in this study that lower values of RCT were associated with a lower content of protein above all in the summer season; however, our results do not correspond with data published by Jõudu et al (2008); Ikonnen et al (2004) and Sevi et al (2001) who obtained opposite results. This could be partly explained on the base of high summer temperatures recorded in our study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…As mentioned by Daviau et al (2008), the shorter RCT was associated with a decrease in P content and also of casein. It was found out in this study that lower values of RCT were associated with a lower content of protein above all in the summer season; however, our results do not correspond with data published by Jõudu et al (2008); Ikonnen et al (2004) and Sevi et al (2001) who obtained opposite results. This could be partly explained on the base of high summer temperatures recorded in our study.…”
Section: Resultscontrasting
confidence: 99%
“…Dolejš et al (1996) found also the milk fat content depression with air temperature increase. Sevi et al (2001) found high ambient temperatures to adversely aff ect the yield and cheese-making parameters of milk by the clotting time and the rate of clot formation and decreasing clot fi rmness. The photoperiod (i.e.…”
mentioning
confidence: 99%
“…The values of THI above which ewes start to suffer from heat stress seem to be quite different among breeds (Finocchiaro et al, 2005). Solar radiation seems to have a limited effect on milk yield, but a greater effect on yield of casein, fat and clot firmness in the milk of Comisana ewes (Sevi et al, 2001). Even goats are affected by heat stress and responded by reducing milk yield and the content of milk components (Olsson and Dahlborn, 1989).…”
Section: Reproductionmentioning
confidence: 99%
“…might be a reflection of the diurnal fluctuations of the ambient temperature (Table2.) and if the temperature drops at night below 21ºC for 3-6 h, the animal could sufficient opportunity to lose at night all the heat gained from the previous day (Igono et al, 1992;Muller et al, 1994;Sevi et al, 2001). However, night temperatures during these trials have been recorded.…”
Section: Discussion:-mentioning
confidence: 99%